Low Birth, Prematurity, and Pre-Eclampsia as Risk Factors of Neonatal Asphyxia - Kusumaningrum, Remita Yuli; Murti, Bhisma; Prasetya, Hanung (Journal of Maternal and Child Health, 2019)
Background: Asphyxia neonatorum is the condition of an infant who does not breathe spontaneously and regularly immediately after birth. This condition is accompanied by hypoxia, hypercapnia, and ends with acidosis. Long-standing asphyxia can cause brain damage and death. This study aimed to investigate risk factors of asphyxia in Nganjuk Hospital, East Java.Subjects and Method: This was an analytic observational study with a case control design. The study was conducted in Nganjuk Hospital, East Java, in July 2018. A total sample of 150 neonates was selected by fixed disease sampling, consisting of 50 neonates with asphyxia and 1oo neonates without asphyxia. The dependent variable was asphyxia. The independent variables were low birth weight, preterm birth, and pre eclampsia. The data were obtained from medical record and analyzed by a multiple logistic regression.Results: The risk of asphyxia increased with low birth weight (OR= 2.58; 95% CI = 3.80 to 46.15; p<0.001), premature birth (OR= 1.27; 95% CI= 1.23 to 10.25; p= 0.019), and pre-eclampsia (OR= 3.74; 95% CI= 12.54 to 141.05; p <0.001).Conclusions: The risk of asphyxia increases with low birth weight, premature birth, and pre-eclampsia.Keywords: asphyxia, neonates, low birth weight, premature, preeclampsiaCorrespondence:Remita Yuli Kusumaningrum. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: renita.yuli@gmail.com. Mobile: +6281231871222.Journal of Maternal and Child Health (2019), 4(1): 49-54https://doi.org/10.26911/thejmch.2019.04.01.07